Strengthening financial infrastructure - Peter J. Morgan; Mario Lamberte (Asian Development Bank Institute (ADBI), 2012)
This study provides comparative perspectives on the current and prospective situation of financial market development in ASEAN, the PRC, and India, identifies key priorities for strengthening financial infrastructure to promote financial development and regional integration, and produces policy recommendations at the national, sub-regional and regional levels. The four priority areas covered by the study are: market development, opening, and efficiency; financial inclusion; achievement of financial stability; and financial integration.
Keywords: E52; F32; G21; G22; G24; G28; 330; financial market development; financial infrastructure; financial development; regional integration; asean; prc; india; Finanzsektor; Finanzmarktregulierung; Finanzkrise; Marktintegration; ASEAN-Staaten; China; Indien